2018
DOI: 10.1177/1477370818764831
|View full text |Cite
|
Sign up to set email alerts
|

The self-legitimacy of prison staff in Slovenia

Abstract: This paper focuses on the self-legitimacy of prison staff in Slovenia. The primary aim of this study is to identify possible differences between those factors that influence the self-legitimacy of prison officers in different periods, which would confirm the applicability of some of the theoretical assumptions on the unstable nature of self-legitimacy. Possible differences between groups of prison workers will be explored. The results show that perceptions of supervisors' procedural justice, relations with col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 23 publications
(27 reference statements)
1
19
1
Order By: Relevance
“…How far the influence of the correlates of Self-Legitimacy and Support for Rehabilitation might change or remain stable over time was not addressed. Yet, as Hacin, Fields and Meško (2018) have recently shown, such changes are possible. Thus there is an urgent need for longitudinal studies of officers' Self-Legitimacy in order to address the potential importance of stability or change in Self-Legitimacy and its correlates.…”
Section: Limitationsmentioning
confidence: 97%
See 3 more Smart Citations
“…How far the influence of the correlates of Self-Legitimacy and Support for Rehabilitation might change or remain stable over time was not addressed. Yet, as Hacin, Fields and Meško (2018) have recently shown, such changes are possible. Thus there is an urgent need for longitudinal studies of officers' Self-Legitimacy in order to address the potential importance of stability or change in Self-Legitimacy and its correlates.…”
Section: Limitationsmentioning
confidence: 97%
“…Given Barbalet's (2001) argument about the importance of relationships in fostering confidence, it is hypothesized that the quality of interpersonal relations among colleagues will influence officers' confidence in their Self-Legitimacy. Among Slovenian police officers, Hacin, Fields, and Meško (2018) found that perceived positive relations with colleagues enhanced officer Self-Legitimacy. Meško and his colleagues had previously reported similar findings (Meško et al, 2017).…”
Section: Self-legitimacy and Support For Rehabilitationmentioning
confidence: 99%
See 2 more Smart Citations
“…The 'power of the pen' (Crewe 2011a) in Spain, if my analysis is correct, does not lie within the uniformed officers but more in the hands of the treatment personnel. 19 This may help understand why, maybe paradoxically, uniformed officers are better evaluated in Spanish prisons than treatment personnel (similar to other countries, Hacin et al 2019). Probably because the stakes that depend on these latter personnel are much higher, as is the frustration that concurs when prison leave is denied on grounds of failed participation in cognitive behavioral programs.…”
Section: Eligibility Criteria: 'Chasing Carrots'mentioning
confidence: 99%